Peran Literasi Membaca dalam Meningkatkan Minat Baca Siswa - Hartatik, Sri; Ibadurrahman, Ahmad Nabil; Sholihah, Faiqahtus; Masodi, Masodi (Universitas Pahlawan Tuanku Tambusai, 2025)
Reading is the main foundation in literacy development because it not only enriches language skills but also broadens students' horizons. In the context of basic education, reading and writing skills are very important to shape the character and critical thinking skills of students. However, low interest in reading and limited access to information, especially in several regions in Indonesia, are still serious challenges that affect the quality of education and human resource development (UNESCO). This study uses a qualitative approach with a library research type. The data collection process uses a method of finding sources and constructing from various sources, for example books, articles and research that has been done. The aim is to describe the role of reading literacy in increasing children's reading interest in elementary schools. This approach was chosen because researchers wanted to understand in depth how reading literacy activities are implemented and how they impact students' reading interest.